IMPLIKASI RETURN ON EQUITY, RETURN ON ASSET, NET INCOME& DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTI - Rianto, Muhammad Richo (Economic Faculty, Attahiriyah Islamic University, 2018)
The research aims to analyze the effect of Return On Equity (ROE ), Return On Asset (ROA), Net Income (NI) and Debt to Equity (DER) on partially and simultaneously to Return Investment (RI) in property companies. Data were collected from secondary data in the financial documentation of Indonesian Capital Market Directory ( ICMD ) and also can download in the official website of the Indonesian Stock Exchange www. IDX.co.id. Data analysis was using Eviews version 7.1. The results show that: ROE, ROA, NI, and DER simultaneously significant effect on the property company’s stock return, but partially only ROE and DER variable that significantly effects on stock return. Keywords: Return on Equity, Return on Asset, Net Income, Debt to Equity, Return Investment